ARTIFICIAL INTELLIGENCE - Sattorova Khadicha Inayat qizi; Sattarov Inayat Saparbayevich (Western European Studies, 2024)
In this article we will learn what Artificial Intelligence is and where we meet it. We will also find out in which areas it is most often used. We will also look at the advantages and disadvantages of AI.
Keywords: Innovation; human intelligence; artificial intelligence